GSH-Triggered/Photothermal-Enhanced H2S Signaling Molecule Release for Gas Therapy - Xinqiang Liang; Mekhrdod S. Kurboniyon; Yuanhan Zou; Kezong Luo; Shuhong Fang; Pengle Xia; Shufang Ning; Litu Zhang; Chen Wang (MDPI AG, 2023)
Traditional treatment methods for tumors are inefficient and have severe side effects. At present, new therapeutic methods such as phototherapy, chemodynamic therapy, and gasodynamic therapy have been innovatively developed. High concentrations of hydrogen sulfide (H2S) gas exhibit cancer-suppressive effects. Herein, a Prussian blue-loaded tetra-sulfide modified dendritic mesoporous organosilica (PB@DMOS) was rationally constructed with glutathione (GSH)-triggered/photothermal-enhanced H2S signaling molecule release properties for gas therapy. The as-synthesized nanoplatform confined PB nanoparticles in the mesoporous structure of organosilica silica due to electrostatic adsorption. In the case of a GSH overexpressed tumor microenvironment, H2S gas was controllably released. And the temperature increases due to the photothermal effects of PB nanoparticles, further enhancing H2S release. At the same time, PB nanoparticles with excellent hydrogen peroxide catalytic performance also amplified the efficiency of tumor therapy. Thus, a collective nanoplatform with gas therapy/photothermal therapy/catalytic therapy functionalities shows potential promise in terms of efficient tumor therapy.